THE EFFECTIVENESS OF CROSSWORD PUZZLE TO IMPROVE STUDENTS’ SKILL IN WRITING DESCRIPTIVE TEXT AS PRE-WRITING ACTIVITY (ELang | An English Language Education Journal, 2019)
The research paper entitled “ The Effectiveness of Crosword Puzzle to Improve Students’ Skill in Writing Descriptive as Pre-Writing Activity” is intended to fulfill one of the requirments to the English Education Study Program of FKIP UNIBBA for taking Sarjana Pendidikan degree. There are two purposes of this research paper, those are to find out whether or not crossword puzzle is effective to improve students’ skill in writing descriptive text and to know students’responses toward crossword puzzle in teaching writing descriptive text. The writer chose the eighth grade of SMP Negeri 8 Cidaun as the population of this study. The number of sample was 24 students for the experimental group and 24 students for the control group. The result of the pre-test showed that the t-test value was 0.921, where t-table at p=0.05 with Df = N1+N2-2= 46 at the level of significance 0.05 for two tailed was 2.021. Then it could be observed that the t-test was lower than t-table ?0.921 2.021, the Null Hypothesis (Ho) is rejected and the Alternative Hypotheses (Ha) is accepted, stating that there was significant difference in the result between crossword puzzle and conventional method in teaching writing descriptive text. It means that applying crossword puzzle in teaching writing descriptive text to the eighth grade of SMP Negeri 8 Cidaun is effective. Then, the questionnaire was given only to the experimental group. It was calculated and converted into percentage to find out how the students’ responses toward the use of crossword puzzle. The result of the questionnaire showed that almost all of students liked crossword puzzle that applied in teaching writing descriptive text, it can help them to find new vocabulary in writing descriptive text, they did not get any obstacles in writing descriptive text using crossword puzzle, and it can improve their skill in writing descriptive text. It means that almost all of students gave the positive responses toward the use of crossword puzzle to improve their skills in writing descriptive text to the eighth grade of SMP Negeri 8 Cidaun.Key Words:Descriptive Text, Crossword Puzzle and writing.